The Road to Becoming a “Live-Streaming Star”: Ecological Influences on Improvisation Efforts Among Teaching-from-Home Chinese English as a Foreign Language Teachers in the COVID-19 Outbreak - Chen, Ningyang (Social Education Research, 2023)
When the COVID-19 pandemic outbreak threw the world into a public panic, teachers worldwide were challenged to adapt to a new pedagogical ecology as online delivery of classes was widely made a required necessity. This study explores how language teachers responded to the sudden disruption via improvisational endeavours during the first online semester and how their endeavours were influenced by various ecological factors beyond the online classroom. Data were collected using a survey and interviews with English as a Foreign Language (EFL) teachers from three universities in eastern coastal China. The results showed that the participants’ improvisation efforts featured limited preparation and creativity and a lukewarm willingness to try out new things while teaching from home. Ecological influences on the teachers’ improvisation efforts were identified as a multitude of institutional, daily contextual, sociocultural, and personal factors that interacted in complex, less predictable ways. In general, the diverse sources of influence exerted a mixed impact on individual teachers’ improvisation practices and performance. Sociocultural influence, in particular the “live-streaming star” meme, was found to be a unique source of inspiration and support. This exploratory study expands the research of improvisation in educational settings, which has largely been associated with pedagogical innovation to adapt to micro-level changes. In the emergency remote teaching scenario, innovative attempts made by individual teachers were subject to the meso-level and the macro-level ecological influences, which may overwhelm or deter practitioners. Apart from potential theoretical and pedagogical implications, the study offers insights into the nature and impact of crisis-prompted online teaching in and beyond the COVID-19 context.